Mass Transfer by Stent Based Drug Delivery System: An Analytical Study - Seethappa, Jagadeesha; Ramarao, Indira; Keshavamurthy, Madhura; Padmarajaiah, Suma Seethkal (New Ideas Concerning Science and Technology Vol. 9, 2021)
An attempt is made to model the stent based drug delivery by assuming a rectangular channel divided into a lumen region, stent placed in the wall region and porous wall. Velocity, concentration and dispersion coefficient at large time are analytically obtained through modified Gill and Sankarasubramanian approach. The results are graphically depicted. Results show that diffusion coefficient is the main factor which affects the mass transfer. The study carried out here helps in analysing the situation where drug is delivered through a stent to the damaged arterial wall.